ORGANIZATION OF MULTI-PATH ROUTING BY MPLS - Zhukov , I. A.; Klimenko, I. A.; Alenin , O. I. (Problems of Informatization and Management, 2005)
A modified method for dividing packet streams at the border node of the MPLS network and an algorithm for managing FEC tables based on this method are proposed, which makes it possible to increase the efficiency of the MPLS network as a whole.